The Validity of the Plant Identification Guidebook for Important Plant Species in the Lembah Bukit Manjai Tropical Rainforest Biodiversity Park - Nurtamara, Luthfiana; Rezeki, Amalia; Widiyastuti, Dewi Amelia (Universitas Muhammadiyah Palembang, 2026)
Plants play an important role in ecosystems, particularly in tropical rainforest ecosystems. This study aimed to develop a feasible plant identification field guide containing information on morphological descriptions, classifications, and photographs of plants from the Tropical Rainforest Biodiversity Park Area of Lembah Bukit Manjai. The book was developed using the Education Design Research (EDR) method proposed by Plomp & Nieveen. The preliminary research stage involved a needs analysis, the preparation of the field guide framework, and an inventory of plants found in the research area. The prototyping phase consisted of drafting the field guide and conducting validity tests by material and media experts. The validity results of the Important Plant Identification Field Guide in the Lembah Bukit Manjai Biodiversity Park from botanical material experts showed a very valid category (96.185%), while media experts also indicated a very valid result (98.57%). These validity results indicate that the field guide is valid in terms of content feasibility, presentation, and language, as well as media aspects including size, cover design, and content design. Therefore, this field guide can proceed to the assessment phase to evaluate its effectiveness as a contextual learning resource and as a supporting medium for biodiversity conservation in the Tropical Rainforest Biodiversity Park of Lembah Bukit Manjai.